Relational processes enabling the balancing of academic work and motherhood: a grounded theory study with academic women at a South African university - Poulos, Tessa (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
Through the use of contextual data, this research study aims to explicate a theory about the experiences of academic women, who are also mothers, employed at a South African University. The research is interpretive in nature as it explores the women's accounts of the conflicts they face in striving to satisfy the demands of both their scholarly work and family responsibilities within multiple intersecting factors related to their personal/familial circumstances, and the strategic processes they engage in to manage the balance between these competing roles. The study followed a constructivist grounded theory design in an attempt to test the hypo
Keywords: Working mothers -- South Africa -- Grahamstown; Women in education -- South Africa -- Grahamstown; Work and family -- South Africa -- Grahamstown; Rhodes University -- Employees; Motherhood -- South Africa -- Grahamstown; Sex role in the work environment -- South Africa -- Grahamstown